SUPPLY AND DEMAND IDENTIFICATION OF ECOTOURISM SECTOR (Case Study : Kota Bengkulu) - Dhona Shahreza; Maria Wikantari; Dhian Tyas Untari (UNIVERSITAS INDRAPRASTA PGRI, 2014)
Ecotourism is a prospective sektor of Bengkulu, and ecotourism development is the once focus concept to increase economic development. The aim of research is to identify supplay and demand of ecotourism sektor. And object research is Kota Bengkulu as a capital city of Bengkulu and also have a lot of potencial tourismproduct. Primary datas get from Bps Kota Bengkulu dan Dispar Kota Bengkulu. And secoundary datas get from observation at the research object. Descriptifve metode use to interprate data findings. The result of the research is to facilitate government of Kota Bengkulu to create a grand strategy of ecotourism sektor.